2021
DOI: 10.3390/met11071145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of abc Pressing at 573 K on the Microstructure and Martensite Transformation Temperatures in Ti49.8Ni50.2 (at%)

Abstract: This paper presents experimental data on the microstructure and martensite transformation temperatures of Ti49.8Ni50.2 (at%) after abc pressing (multi-axial forging) to different true strains e from 1.84 to 9.55 at 573 K. The data show that increasing the true strain results in grain–subgrain refinement on different scales at a time. With e = 9.55 at 573 K, the average grain–subgrain size measured approximately 130 nm. Decreasing the abc pressing temperature from 723 to 573 K caused a decrease in all martensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 35 publications
0
11
0
2
Order By: Relevance
“…In addition, the composition of the microstructure shown in Figure 2a contains both grains-subgrains with a two-phase structure R + B19 and grains-subgrains in which either a martensitic R-phase or a martensitic B19 -phase are observed. The more detailed analysis of phase state and microstructure in Ti 49.8 Ni 50.2 alloy after abc pressing at 573 K are presented in [61].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the composition of the microstructure shown in Figure 2a contains both grains-subgrains with a two-phase structure R + B19 and grains-subgrains in which either a martensitic R-phase or a martensitic B19 -phase are observed. The more detailed analysis of phase state and microstructure in Ti 49.8 Ni 50.2 alloy after abc pressing at 573 K are presented in [61].…”
Section: Resultsmentioning
confidence: 99%
“…As noted in the introduction, the evolution of the microstructure of the Ti 49.8 Ni 50.2 alloy samples was studied in [14] as a function of the abc-strain specified at 573 K. It was found that the refinement of the grain-subgrain microstructure occurs at two structuralscale levels. The first level (denoted in [14] as a macrolevel) is large grains of initial samples with high-angle grain boundaries. The average sizes of these large grains are denoted as D. The second level (denoted in [14] as the microlevel) is the level of the grain-subgrain structure inside large grains.…”
Section: Microstructurementioning
confidence: 99%
“…This caused an increase in the yield stress, σ y , and ultimate tensile strength, σ UTS , by 2.3 and 1.5 times, respectively. One of the well-known methods of severe plastic deformation, which makes it possible to obtain an ultrafine-grained structure in metals and alloys, is the forging method with a change in the deformation axis in three mutually orthogonal directions, which is called "multi-axial forging" or "abc-pressing" [9][10][11][12][13][14]. The abbreviation "abc-pressing" was used in further text.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimal mechanical performance of the alloy was shown to be achieved via β-annealing at 1005 • C for 70 min, followed by air cooling to room temperature and aging at 722 • C for 2 h with subsequent air cooling to room temperature. Kashin et al reported the results of the experimental study of the microstructure and martensite transformations of Ti 49.8 Ni 50.2 alloy after abc pressing at 573 K [7]. They showed that increasing the true strain resulted in grain-subgrain refinement on different scales and proposed possible mechanisms for this effect.…”
Section: Contributionsmentioning
confidence: 99%